Integrasi Seni Kuno dan Tantangan Enkripsi Modern melalui Kajian Ulang Teknik Kriptanalisis Al-Kindi - Anandari, Anatansyah Ayomi (Historia Madania: Jurnal Ilmu Sejarah, 2023)
This study aims to review the cryptanalysis techniques introduced by Al-Kindi, an ancient cryptographic figure, by relating them to the modern encryption challenges faced today. The method used involves an analysis of the literature on Al-Kindi's works which are relevant in cryptanalysis, such as “Risalah al-Mu'atabarah". In addition, the ancient cryptanalysis techniques introduced by Al-Kindi are also analyzed in the context of complex modern encryption challenges. The results of this study indicate that the cryptographic principles proposed by Al-Kindi, such as the substitution method, the transposition method, and the need for a strong secret key, still have relevance in overcoming modern encryption challenges. The method of substitution and transposition introduced by Al-Kindi can be adapted in letter frequency analysis and structural analysis to decode complex codes. The principle of needing a strong secret key also remains important in protecting data and communications in the modern digital era. The cryptographic principles introduced by Al-Kindi can be applied in overcoming the complexity of the current encryption system. This research provides new insights into how to apply ancient cryptographic principles to crack complex codes and improve information security in the ever-evolving digital age.